Iwan Fals, Music, and the Voice of Resistance - Muhammad Yusran Darmawan (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
This article is based on the assumption of a connection between popular music and the political situation in Indonesia. A singer has a function as a political actor, especially in the way these performers use music as a social weapon or tool –and even sometimes as a call to change, challenge, or overthrow the existing government or socio-economic conditions that they consider to be unjust systems. The purpose of this paper is to explain the life of Iwan Fals as a contemporary hero who inspires many people to be critical of authority. He has always been the voice of Indonesia's grassroots movement since the New Order era, but until now, he has preferred not to be its formal leader. He just keeps doing what he does best - singing and cheering - and maintaining the qualities of his song and conviction that keeps his fans loyal to him. Under the New Order, control of the arts and media by the government was mixed and inconsistent, but generally, Indonesia enjoyed a thriving and vibrant artistic scene, including music. Between the mid-1960s and 1990s, Indonesia developed a wide variety of popular music styles, some of which proved to be conducive and supportive to socio-political comments and critiques. Popular music became a major component of the background for daily life. In Indonesia, popular music became a tool of resistance to the government. Iwan Fals played an important role in this resistance.